Particles Precipitation in Ti‐ and Al‐Deoxidized Hadfield Steels. Issue 10 (4th March 2016) - Siafakas, Dimitrios; Matsushita, Taishi; Lauenstein, Åsa; Ekerot, Sven; Jarfors, Anders E. W.
Abstract : The characteristics and precipitation mechanism of particles in titanium‐ and aluminum‐treated Hadfield steel casted during pilot‐scale experiments have been studied. Light Optical Microscopy (LOM), Scanning Electron Microscopy (SEM), and Energy Dispersive X‐ray Spectroscopy (EDS) are utilized for the particle analysis and characterization. Additionally, thermodynamic equilibrium calculations are performed using Thermo‐Calc software. Aluminum oxides, titanium carbon nitrides, titanium carbides, and manganese sulfides are the main types of particles found. The order of precipitation during solidification and chemical composition range of each type of particle are determined. Aluminum oxides are found to act as nucleation sites for titanium carbon nitrides. Thermodynamic equilibrium calculations for particles characteristics are in good agreement with the experimental findings. Titanium carbides are found to form during initial stages of the ferro‐titanium additions dissolution. Abstract : The in situ particles precipitation in Ti‐ and Al‐deoxidized Hadfield steel is investigated . The present study explores the type, sequence of formation, and chemical composition as well as the mechanisms behind the in situ formation of particles during traditional deoxidation treatment of Hadfield steels. SEM–EDS and Thermo‐Calc are utilized for the analysis.